PENGARUH PENGGUNAAN MEDIA DAKIMBER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI SD BAITU ILMIN SURABAYA - Khairunnisa Sa'diyah; Sunanto; Rudi Umar Susanto; Afib Rulyansah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of fourth-grade stu dents at SD Baitu Ilmin Surabaya in Indonesian language subjects, specifically regarding the prefix "ber-", due to conventional lecturing methods and the lack of instructional media. This study aims to determine the effect of using Dakimber media (dakon imbuhan ber-) on student learning outcomes in Indonesian subjects. The research method used is quantitative with a Pre-Experimental design (one group pretest-posttest) involving 20 students as research subjects. The research instruments were tests (pretest and posttest) analyzed using the Paired Sample T-Test via SPSS 25. The results showed an increase in the average learning outcome score from 47.5 during the pretest to 88.8 during the posttest. Statistical analysis revealed a Sig. (2-tailed) value of 0.000 (< 0.05), leading to the conclusion that the use of Dakimber media has a significant effect on improving the learning outcomes of fourth-grade students on prefix material. This media is effective in encouraging active student participation through engaging educational games.